Checklist for commercially important food fishes of Parangipettai Southeast Coast of India - Kadharsha, Kudus; Khan, Syed Ajmal; Lyla, Somasundharanair; Mohanchander, Ponnuvel; John, Akbar (Zibeline International Publishing, 2018)
A checklist for commercially important food fishes from Parangipettai, Southeast coast of India is presented (lat. 11̊ 30’ N, long. 79̊ 46’ E). This comprises 93 species belonging to 57 genera and 42 families currently known from the area, which are all of commercially valuable. We provided a synthesis of the taxonomical work carried out until now that could guide to future research.